Surfactant-Free Precious Metal Colloidal Nanoparticles for Catalysis - Quinson, Jonathan (Frontiers in Nanotechnology, 2021)
Colloidal syntheses of nanoparticles (NPs) are one of the preferred approaches to prepare precious metal catalysts. Unfortunately, most colloidal syntheses developed require stabilizing agents to avoid NP agglomeration and/or control NP size and morphology. While these surfactants can bring positive features, they typically block catalytically active sites on the NP surface. As a consequence, these additives often need to be removed by energy and/or time consuming steps, at the risk of complicating the synthesis, introducing irreproducibility and negatively altering the structure and properties of the prepared catalysts. Fortunately, several surfactant-free colloidal syntheses have been reported and are being developed. This Mini Review addresses the challenges in defining a surfactant-free colloidal synthesis of NPs and survey established and emerging strategies to obtain surfactant-free colloidal precious metal NPs. A focus is given to approaches that show promising features to bridge the gap between fundamental and applied research towards industrial applications.